2005
DOI: 10.1021/es048560b
|View full text |Cite
|
Sign up to set email alerts
|

Designing Pd-on-Au Bimetallic Nanoparticle Catalysts for Trichloroethene Hydrodechlorination

Abstract: Alumina-supported palladium (Pd) catalysts have previously been shown to hydrodechlorinate trichloroethene (TCE) and other chlorinated compounds in water, at room temperature, and in the presence of hydrogen. The feasibility of this catalytic technology to remediate groundwater of halogenated compounds can be improved by re-designing the Pd material in order to increase catalytic activity. We synthesized and characterized Pd supported on gold nanoparticles (Au NPs) of different Pd loadings. In all cases, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
272
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(282 citation statements)
references
References 54 publications
8
272
0
2
Order By: Relevance
“…Both Au@Pd and Au@Pt particles have been studied, primarily as catalysts, with their optical properties only utilized as tools for characterization. Li et al [209] produced Au@Pd nanoparticles by thermal decomposition of PdCl 2 on existing Au nanoparticle cores, whilst Nutt et al [210] deposited Pd onto a colloid of Au nanoparticles. The precipitation of Pd onto Au nanorod cores has also been demon strated, and as expected, the longitudinal and transverse resonances of the nanorod cores were attenuated by increasing Pd shell thickness until they completely disappeared.…”
Section: Metallic Coatingsmentioning
confidence: 99%
“…Both Au@Pd and Au@Pt particles have been studied, primarily as catalysts, with their optical properties only utilized as tools for characterization. Li et al [209] produced Au@Pd nanoparticles by thermal decomposition of PdCl 2 on existing Au nanoparticle cores, whilst Nutt et al [210] deposited Pd onto a colloid of Au nanoparticles. The precipitation of Pd onto Au nanorod cores has also been demon strated, and as expected, the longitudinal and transverse resonances of the nanorod cores were attenuated by increasing Pd shell thickness until they completely disappeared.…”
Section: Metallic Coatingsmentioning
confidence: 99%
“…Bonarowska et al [29] have demonstrated that the preparation of carbon supported Au-Pd by a comparable impregnation/redox reaction method leads to alloy formation and a higher selectivity to CH 2 F 2 in the HDC of CFC-12 when compared with Pd/SiO 2 . Nutt et al [32] reported enhanced C 2 HCl 3 HDC performance over Au-Pd where Au alone was inactive. Although we have no direct evidence of surface alloy formation in our Au-Ni/Al 2 O 3 sample, HDC is favored by a more homogenous distribution of both metals on the surface and the promotional response may result from electronic or geometric effects.…”
Section: Catalyst Structural Characteristicsmentioning
confidence: 99%
“…Of direct relevance to this study, Bonarowska et al have employed carbon [29,30] and SiO 2 supported [31] Au-Pd to dehalogenate CCl 2 F 2 (CFC-12) where the incorporation of Au had a direct impact on dehalogenation selectivity (to CH 2 F 2 ). Nutt et al [32] reported enhanced liquid-phase C 2 HCl 3 dechlorination over Au-Pd/Al 2 O 3 when compared with Pd/Al 2 O 3 , which they attributed to Au-Pd interactions; this was also the case for unsupported Au-Pd nanoparticles. [33] With regard to Ni-Au bimetallic systems, the following pertinent studies should be noted: a) Rousset et al [34] have generated supported bimetallic Au 0.5 Ni 0.5 clusters (2.3 nm size) on a carbon film by laser vaporization of the bulk alloy; b) Molenbroek and co-workers [35,36] have examined the action of Ni-Au/SiO 2 , prepared by impregnating the reduced monometallic Ni catalyst with an aqueous solution of 3 ] in butane steam-reforming and reported Ni-Au alloy formation at a reduction temperature of 823 K; c) Triantafyllopoulos and Neophytides [37] have noted that the addition of Au (as HAuCl 4 ) to Ni/YSZ serves to suppress carbon deposition during methane steam reforming, an effect that extends to Au-Ni/MgAl 2 O 4 ; [38] d) Venugopal et al [24] have reported high water-gas shift activities for Au-Ni/Fe 2 O 3 , prepared by deposition/coprecipitation, as a result of surface Au-Ni interactions; e) Vasil'kov et al [39] recorded an increase in isomerization activity over Au-Ni/SiO 2 that they ascribed to surface Au-Ni interactions.…”
Section: Introductionmentioning
confidence: 97%
“…It has been proven, for instance, that these nanoparticles are excelent catalysts of trichloroethene (TCE), achieving a higher activity than both pure palladium nanoparticles and catalysts based on bulk palladium; this makes Au-Pd nanoparticles extremely effective agents for the remediation of various inorganic and organic groundwater contaminants. 2 More recently, Au-Pd alloys have been found to be outsanding catalysts for the hydrogenation of naphthalene and toluene, 3 which makes them important for the improvement of diesel fuels. There is also interest in the development of Au-Pd catalysts for the oxidation of alcohols to aldehydes.…”
Section: Introductionmentioning
confidence: 99%